PENGARUH LITERASI KEUANGAN DAN INKLUSI KEUANGAN DIGITAL TERHADAP KINERJA KEUANGAN UMKM DI KOTA DENPASAR - I Putu Santika; Ica Rika Candraningrat; Putu Yusi Pramandari (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2026)
This study analyzes the influence of financial literacy and digital financial inclusion on the financial performance of MSMEs in Denpasar City, considering the mediating role of digital financial inclusion. This quantitative research employed a cross-sectional approach using purposive sampling of 150 MSME owners across four sub-districts in Denpasar City. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling (SEM) with SmartPLS 3.0. Financial literacy significantly influences financial performance (β = 0.326, t = 4.127, p < 0.001). Digital financial inclusion significantly affects financial performance (β = 0.418, t = 5.293, p < 0.001). Digital financial inclusion partially mediates the relationship between financial literacy and financial performance (indirect effect = 0.218, p < 0.001, VAF = 40.1%). Significant differences in financial performance were found based on business sector (p = 0.024), but not by gender, age, or education level. Simultaneous improvement of financial literacy and adoption of digital financial technology can enhance MSME financial performance in Denpasar City. The research model explains 58.3% of the variation in MSME financial performance).